Meaning Visualization: A Saussurean Semiotic Analysis of the Film Merry Riana - Ramadhani, Zahra Shafa; Musa, Purnawarman; Pertiwi, Cholidah Astri (Universitas Pendidikan Nasional, 2023)
The objective of this study is to determine the motivational messages that are sent in the movie